2022
DOI: 10.1039/d2me00066k
|View full text |Cite
|
Sign up to set email alerts
|

Digital light processing 3D printing of hydrogels: a minireview

Abstract: The rapid development of three-dimensional (3D) printing hydrogel materials into sophisticated constructs has led to considerable progress in the fields of tissue engineering, soft actuators/robots, flexible electronics, etc. Notably, digital...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 107 publications
0
23
0
Order By: Relevance
“…DLP printing employs a layer‐by‐layer polymerization process, in which hydrogel thin layers can be fabricated in less than 1 min. More importantly, spatiotemporal light control in the DLP allows controlling the degree of curing, consequently the material properties gradient along in‐plane and through‐plane directions in a pixelated manner 72–78 . For example, grayscale photo‐printing uses omnidirectional light control to introduce material heterogeneity into a photo curable materials and allows the production of hydrogels with varied properties using the single vat of resin (Figure 3A).…”
Section: Preparation Methods For Hydrogel Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…DLP printing employs a layer‐by‐layer polymerization process, in which hydrogel thin layers can be fabricated in less than 1 min. More importantly, spatiotemporal light control in the DLP allows controlling the degree of curing, consequently the material properties gradient along in‐plane and through‐plane directions in a pixelated manner 72–78 . For example, grayscale photo‐printing uses omnidirectional light control to introduce material heterogeneity into a photo curable materials and allows the production of hydrogels with varied properties using the single vat of resin (Figure 3A).…”
Section: Preparation Methods For Hydrogel Filmsmentioning
confidence: 99%
“…More importantly, spatiotemporal light control in the DLP allows controlling the degree of curing, consequently the material properties gradient along inplane and through-plane directions in a pixelated manner. [72][73][74][75][76][77][78] For example, grayscale photo-printing uses omnidirectional light control to introduce material heterogeneity into a photo curable materials and allows the production of hydrogels with varied properties using the single vat of resin (Figure 3A). 79 Extrusion-based 3D printing is a widely used printing technology for hydrogel materials, which involves a structure-forming step based on the extrusion of ink and subsequent structure fixation.…”
Section: D Printing For Fabrication Of Hydrogel Filmsmentioning
confidence: 99%
“…188 Ding et al recently reviewed a wider array of light crosslinkable hydrogels that are compatible with DLP-SLA 3D printing systems. 189 While most of these resins are highly biocompatible, their ability to make the small, enclosed microfluidic channels and thin membranes common in OoC applications is less well understood and has not been as widely reported. Some of the smallest such features using a biomaterial based resin are those of Grigoryan et al, which demonstrated 150 μm thick membrane-like fin elements used in their perfusable 3D static mixer and 200 μm channels as part of their distal lung subunit.…”
Section: Biomaterial-based Resinsmentioning
confidence: 99%
“…188 Ding et al recently reviewed a wider array of light crosslinkable hydrogels that are compatible with DLP–SLA 3D printing systems. 189…”
Section: Considerations For Fabrication Of 3d Printed Ooc Devicesmentioning
confidence: 99%
“…For example, SLA uses a laser, and digital light processing (DLP) uses a projector. DLP can be further divided according to the modeling direction of the build plate: constrained surface (i.e., bottom-up) [5] and free surface (i.e., top-down) [6]. Free-surface DLP covers the build plate with the photosensitive liquid resin for curing and molding, which are then stacked step by step in layers using a lifting platform.…”
Section: Introductionmentioning
confidence: 99%